Improved clinical outcomes of tocilizumab cyclophosphamide for IgG4-related disease: insights from a prospective IgG4-related disease registry - Ji Zongfei; Zhang Lijuan; Sun Ying; Liu Dongmei; Wu Sifan; Kong Xiufang; Ma Lingying; Liu Yun; Ma Lili; Chen Huiyong; Jiang Lindi (SAGE Publishing, 2021)
Objective: To compare the clinical outcomes of patients with active immunoglobulin G (IgG) 4 related disease (IgG4-RD) receiving tocilizumab versus those receiving cyclophosphamide (CYC). Methods: This IgG4-RD registry study was a prospective cohort study conducted among patients with active IgG4-RD hospitalized at Zhongshan Hospital, Fudan University. Patients who were treated with tocilizumab or CYC along with glucocorticoids (GCs) were enrolled. All participants were followed up at the hospital clinic at 3 and 6 months after discharge. Primary clinical outcomes were measured via the IgG4-RD responder index (RI), complete response (CR), and partial response (PR), as well as side effects. Results: From January 2015 to June 2020, 29 patients enrolled. Fourteen and 15 patients were treated with tocilizumab and CYC, respectively. At the 6-month follow-up, disease activity parameters including erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), IgG4, and IgG4-RD RI, decreased significantly in both groups. At 6 months, tocilizumab demonstrated its superiority, with 50% of patients achieving CR in the Tocilizumab group versus 20% in the CYC group. However, no statistical significance was identified ( p  = 0.128). The GC dosage at 6 months was significantly lower in the tocilizumab group than in the CYC group [10 (9.4-15) mg/d versus 15 (15-15) mg/d, p  = 0.025]. In the CYC group, two patients experienced lumbar vertebral compression fractures related to GCs. Other patients in both groups showed mild adverse effects. Conclusions: Tocilizumab could be a better steroid-sparing agent, with a comparable curative effect and tolerance, than CYC, in the treatment of IgG4-RD.